2016
DOI: 10.1177/0885066616679974
|View full text |Cite
|
Sign up to set email alerts
|

I-TRACH: Validating A Tool for Predicting Prolonged Mechanical Ventilation

Abstract: Similar to our previous retrospective study, these findings validate I-TRACH in determining the subsequent need for MV >7 and >14 days at the time of intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
1
25
1
1
Order By: Relevance
“…The adjusted OR of death in the high shedding group versus the low shedding reference group was 0.43 (95% CI = 0.01–1.67, P = 0.23) for the subgroup with ARDS and 0.53 (95% CI = 0.20–1.30, P = 0.17) for the entire cohort, suggestive that the relationship between GAG shedding and days on mechanical ventilation was not confounded by mortality. Given that airspace GAG concentrations were determined using HMEF collected within 24 hours of intubation, these findings may be useful for the care of ICU patients, as there are few clinically available tools to predict the duration of respiratory failure at the bedside ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The adjusted OR of death in the high shedding group versus the low shedding reference group was 0.43 (95% CI = 0.01–1.67, P = 0.23) for the subgroup with ARDS and 0.53 (95% CI = 0.20–1.30, P = 0.17) for the entire cohort, suggestive that the relationship between GAG shedding and days on mechanical ventilation was not confounded by mortality. Given that airspace GAG concentrations were determined using HMEF collected within 24 hours of intubation, these findings may be useful for the care of ICU patients, as there are few clinically available tools to predict the duration of respiratory failure at the bedside ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of diagnosis profiles with other studies is difficult due to different methods of documenting a primary ICU diagnosis 7,9,18,19 . However, earlier studies also report sepsis as a primary reason of PMV 11,20 . The only difference in this study found between mechanical ventilation ≥7-21 days and PMV >21 days was that a primary ICU diagnosis of pancreatitis or respiratory insufficiency was more likely to require PMV >21 days.…”
Section: Use Of Bed Daysmentioning
confidence: 96%
“…In addition to patients in medical or surgical ICUs without further specification, there were studies that included patients surviving sepsis with respiratory failure, tracheotomized patients undergoing MV, patients admitted to respiratory ICUs, or patients admitted to the ICU after cardiac surgery. Risk factors identified as relevant for PMV or prolonged weaning include age [1,16], comorbidities (previous stroke, renal impairment, poor cardiac function, chronic obstructive pulmonary disease [COPD]) [17][18][19][20][21] and various laboratory parameters (low platelets, elevated blood urea nitrogen, elevated creatinine, low serum albumin, elevated blood glucose levels or hypernatremia) [16, 18-20, 22, 23]. Blood gas analysis values (lower HCO 3 or pH values or higher PaCO 2 ) as well as parameters of ventilator settings (FiO 2 ≥ 0.39, level of PEEP) [19,24] or gas exchange (PaO 2 /FiO 2 <200 mm Hg) [16] were also identified as relevant.…”
Section: Risk Factors For Prolonged MVmentioning
confidence: 99%